EUS-guided hepaticogastrostomy combined with fine-gauge antegrade stenting: a pilot study - Ogura, Takeshi; Masuda, Daisuke; Imoto, Akira; Takeushi, Toshihisa; Kamiyama, Rieko; Mohamed, Malak; Umegaki, Eiji; Higuchi, Kazuhide (Endoscopy, 2014)
Background and study aim: To minimize bile leakage and avoid possible death because of stent migration in endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS), we have recently combined EUS-HGS with EUS-guided antegrade stenting (EUS-AS) of the biliary obstruction using a novel uncovered metallic stent with a fine-gauge delivery system. In this pilot study, we evaluated the feasibility and adverse events associated with this combination therapy using the novel stent. Patients and methods: We performed EUS-guided antegrade stenting and hepaticogastrostomy in 12 consecutive patients. Results: The novel EUS-AS stent was placed across the ampulla of Vater in 8 patients and above the ampulla in 4. Technical and functional success rates were 100 %. In addition, the insertion of the first stent was achieved in all patients without dilation of the fistula between stomach and intrahepatic bile duct. Although 1 patient experienced mild pancreatitis, adverse events such as bile peritonitis or stent dysfunction did not occur during follow-up (mean 122 days, range 62 – 210 days). Conclusion: This method appears to safely and effectively avoid adverse events associated with EUS-HGS.